Role of Connexin-Based Gap Junction Channels in Communication of Myelin Sheath in Schwann Cells - Cisterna, Bruno A.; Arroyo, Pablo; Puebla, Carlos (Frontiers in Cellular Neuroscience, 2019)
The capacity of peripheral nerves to conduct action potentials along great distances and quickly recover following damage is mainly due to Schwann cells (SCs), the most abundant glial cells of the peripheral nervous system. SCs wrap multiple times around an axonal segment, forming a myelin sheath, allowing a significant increase in action potentials conduction by insulating the axons. Mature myelin consists of compact and non-compact (or cytoplasmic) myelin zones. Non-compact myelin is found in paranodal loops bordering nodes of Ranvier, and in innermost and outermost cytoplasmic tongues, and is the region in which Schmidt-Lanterman incisures (continuous spirals of overlapping cytoplasmic expansions within areas of compact myelin) are located. Using different technologies, it was shown that the layers of non-compact myelin could be connected to each other by gap junction channels (GJCs), formed by connexin 32 (Cx32), and their relative abundance allows transfer of ions and different small molecules. Likewise, Cx29 is expressed in the innermost layer of myelin sheath where it does not form GJCs but it colocalizes with Kv1, which implies that the SCs play an active role in the electrical condition in mammals. The critical role of GJCs in the functioning of myelinating SCs is evident in Charcot-Marie-Tooth disease (CMT), X-linked form 1 (CMTX1), which is caused by mutations in the gap junction protein beta 1 gene that codes for Cx32. Although the management of CMT symptoms is currently supportive, recently a method for targeted gene delivery to myelinating cells rescues the phenotype in KO-Cx32 mice, a model of CMTX1. In this mini-review, we show the current knowledge about the role of Cxs in myelin-forming SCs and summarize the recent discoveries that may become a real possibility for patients with disorders such as CMT.